New optical nova candidate in M31 - Stefanescu, A.; Pietsch, W.; Burwitz, V.; Hatzidimitriou, D.; Pöpsel, J.; Binnewies, S.; Ruder, H.; Papamastorakis, G. (The Astronomer's Telegram, 2007)
We report the discovery of an optical nova candidate in M 31 on ten stacked R filter CCD images (each with 60 sec exposure) obtained on 2007 Aug 30.018 with an R magnitude of 17.8 obtained at the 60cm f/8 Ganymed telescope located at Skinakas Observatory, Crete, Greece, using a ST10XME CCD Camera. The object is confirmed on CCD images with the same telescope using a broad H-alpha filter (4*120 s stacked, 17.7 mag) obtained on 2007 Aug 30.029.
Keywords: Novae; Optical